Developing tomorrow's managers today: An examination of superior/subordinate developmental relationships - E. D. Schmikl (South African Journal of Business Management, 1984)
Although the Mentorship concept has been around for many centuries it is being examined with renewed interest by organizational development and human resources specialists. Researchers have found that organizations that are characterized by excellence have policies that promote a corporate organizational culture in which management makes a conscious effort to develop young men and women with leadership talent. The conscious attempt by superiors to grow one or more subordinates results from the fact that two-thirds of outstanding successful executives claimed to have had mentors in their careers. Superior-subordinate developmental relationships do not always succeed. Some relationships blossom, others break down, and many never even develop at all. Some studies reveal that there are good and poor mentors and special kinds of subordinates. These studies focus on the characteristics of the mentor and the protégé where developmental relationships have blossomed and also failed. It is furthermore suggested that where mentor-protégé relationships have blossomed that this may be due to a supportive organizational culture and the fact that superiors and their subordinates had matching interactive styles that promoted interaction in their interpersonal relationships. The latter has been illustrated from managerial action profiling research. More research is required to establish the important link between the characteristics of effective superiors and subordinates, organizational culture, and interpersonal interaction styles within superior-subordinate developmental relationships. It is argued that the effective management of superior-subordinate developmental relationships within organizations is critical if organizations are to remain productive and profitable, and survive the challenges of the next two decades.
Keywords: 650